INTEGRASI NILAI SPIRITUAL, INTELEKTUAL DAN MORAL DALAM KONSEP PENDIDIKAN SAID NURSI - Faiz, Muhammad (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2013)
Bediuzzaman Said Nursi (1877-1960) was an Islamic revivalist who lived in the last period of the Ottoman caliphate in Turkey. He emerged with his book